1981
DOI: 10.1159/000131573
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal evolution in African megachiroptera: G- and C-band assessment of the magnitude of change in similar standard karyotypes

Abstract: Differential staining (G- and C-banding) is used to assess magnitude of chromosomal variation in eight species of African megachiropterans. These data are compared with those suggested by standard karyotypic studies, and it is concluded that in this example standard methods underestimate chromosomal variation by a factor greater than 4.5. The implication of these data is that models constructed from patterns of chromosomal evolution in standard karyotypes need to be evaluated in light of in-depth studies based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…This is due primarily to the superior methods of chromosome harvest available in these species (e.g., Lee and Elder 1980). Collectively , the vertebrate data have shown that variation in both heterochromatin amount and chromosomal position is or can be extensive both within and across phyletic groups (Arnason 1974, Yosida 1975, Mascarello and Mazrimas 1977, Pathak and Wurster-Hill 1977, Schmid 1978a, b, Mengden 1981, Haiduk et al 1981, Baverstock et al 1982, Patton and Sherwood 1982. Most species invariably possess C-bands at or around the centromeres (pro centric), and frequently at the chromosome tips (telomeric).…”
mentioning
confidence: 99%
“…This is due primarily to the superior methods of chromosome harvest available in these species (e.g., Lee and Elder 1980). Collectively , the vertebrate data have shown that variation in both heterochromatin amount and chromosomal position is or can be extensive both within and across phyletic groups (Arnason 1974, Yosida 1975, Mascarello and Mazrimas 1977, Pathak and Wurster-Hill 1977, Schmid 1978a, b, Mengden 1981, Haiduk et al 1981, Baverstock et al 1982, Patton and Sherwood 1982. Most species invariably possess C-bands at or around the centromeres (pro centric), and frequently at the chromosome tips (telomeric).…”
mentioning
confidence: 99%
“…However, C-banding studies have demonstrated the presence of pericentromeric heterochromatic regions in most karyotypes of bat species analysed to date, with similar size to those described in most of the mammal species (Pathak et al, 1973;Bickham, 1979;Haiduk et al, 1981;Morielle-Versute et al, 1996;Santos and Souza, 1998;Volleth et al, 1999;Volleth et al, 2001).…”
Section: Genomic Content Of Satellite Dnamentioning
confidence: 61%
“…It has been suggested that the difference in the nuclear content of bats in relation to other mammalian groups is mainly because of their lack of repetitive DNA sequences (Van Den Bussche et al, 1995). However, C-band studies in bat chromosomes have revealed several species with large amounts of heterochromatic regions (Haiduk et al, 1981;MorielleVersute et al, 1996;Volleth et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple inversions in chromosome 6 have been noted in Peromyscus (Bobbins and Baker, 1981;Rogers, 1983). With the resolution of Gbands available to us it is impossible to distinguish the inversion in chromosome 6 in Reithrodontomys from that found in some species of Peromyscus.…”
Section: Discussionmentioning
confidence: 92%
“…In this example, data on differentially-stained chromosomes have provided a magnitude of information that could not have been afforded by standard karyotypic preparations. Banding studies of pteropodid and phyllostomid bats (Patton and Baker, 1978;Baker and Bickham, 1980;Haiduk et al, 1981;Haiduk and Baker, 1982) and oryzomyine rodents (Baker et al, 1983) are additional examples that suggest caution in interpreting chromosomal evolution based on standard chromosomal morphology.…”
Section: Discussionmentioning
confidence: 99%